Rejection sensitivity and interaction quality in everyday life. (December 2021) - Bayer, Joseph B.; Triệu, Penny; Ellison, Nicole; Schoenebeck, Sarita Y.; Falk, Emily B.
The elevated satisfaction that comes from interacting with close ties, as opposed to distal ties, is well-established in past research. What remains less clear is how the quality of daily interactions between close versus distal ties may vary as a function of personality. Drawing on data from a 2-week experience sampling study ( N = 108 participants, N = 7755 observations), we consider how trait rejection sensitivity (RS)—or the tendency to worry about potential social rejection—interacts with perceived closeness and interaction channel (i.e., face-to-face vs. technology-mediated) in daily life. We find that individuals who are high (vs. low) in rejection sensitivity not only view distal tie interactions as less satisfying, they also perceive close tie exchanges as more enjoyable and supportive—but only for technology-mediated (vs. face-to-face) interactions. We also find that individuals who are high in rejection sensitivity have higher variability in the perceived quality of their interactions. These findings demonstrate the interlocked factors of personality tendencies, perceived closeness, and interaction channel in shaping the variability in the quality of daily interactions.